1996
DOI: 10.1159/000169046
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriately High Plasma Renin Activity Accompanies Chronic Loss of Renal Function

Abstract: Stimulation of both the systemic and local renin-angiotensin systems participates in the pathogenesis of tissue injury observed in experimental renal disease. However, substantial information demonstrating excessive activation of the renin-angiotensin system in patients with chronic renal disease is not available in spite of the well-established role of this system in the progression of renal damage. This investigation examined the plasma renin activity (PRA) and the ratio of this parameter to the simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…Although a few patients were receiving angiotensin-converting enzyme inhibitor (ACEI) therapy, which may have contributed to elevate PRA values, more importantly none of the values was <25th percentile of the reference group and thus do not conform to a state of volume expansion. Previous studies evaluating PRA levels in patients with CKD but without congestive heart failure are limited, and have consistently shown progressively higher PRA values with declining GFR levels [ 34 ] and a markedly increased ratio of PRA to the simultaneously measured GFR compared with normal subjects [ 35 ]. These findings suggest activation of the RAAS as a result of the loss of functioning nephrons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few patients were receiving angiotensin-converting enzyme inhibitor (ACEI) therapy, which may have contributed to elevate PRA values, more importantly none of the values was <25th percentile of the reference group and thus do not conform to a state of volume expansion. Previous studies evaluating PRA levels in patients with CKD but without congestive heart failure are limited, and have consistently shown progressively higher PRA values with declining GFR levels [ 34 ] and a markedly increased ratio of PRA to the simultaneously measured GFR compared with normal subjects [ 35 ]. These findings suggest activation of the RAAS as a result of the loss of functioning nephrons.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive elevations of PRA levels have also been observed in patients with heart failure and reduced renal function even without ACEI or angiotensin-receptor blockers treatment [ 36 ], and who concomitantly displayed higher FGF23 levels [ 37 ]. These observations raise the possibility that as a result of the renal dysfunction, FGF23 could contribute to RAAS activation [ 10 ] with subsequent increase in PRA [ 34 , 35 ], and activation of the intrarenal RAAS [ 38 ] may contribute to the progression of CKD and hypertension. Our patients with reduced GFR demonstrated significantly higher FGF23 and PRA levels, concurrent with lower concentrations of 1,25(OH) 2 D, underscoring the complex relationships between FGF23, vitamin D and the RAAS independent of overt volume changes, as observed in uremic animals [ 39 , 40 ] and in patients with genetically deficient 1,25(OH) 2 D secretion who display low or undetectable 1,25(OH) 2 D levels, elevated FGF23 and increased PRA values [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…40,41 As for RAS activation, inappropriate high level of plasma renin activity has been reported in patients with CKD. 42 High angiotensin II level can increase atrial pressure, promote atrial fibrosis, and modulate ion channels, all of which contribute to the genesis of AF. 13,43 Moreover, AF itself could promote the expression of angiotensin-converting enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, three recent large-scaled studies confirmed the high prevalence and prognostic relevance of WRF also for patients with chronic stable heart failure. 4,6,17 Although the pathogenesis of the cardio-renal syndrome still is a matter of speculation, besides haemodynamics, vascular factors and medication effects neurohumoral activation may be a key link between the two diseases, [20][21][22] hence, placing natriuretic peptides in the focus of interest. Most previous studies examined natriuretic peptides in patients with heart failure and renal dysfunction in cross-sectional analyses showing elevated levels for both diseases.…”
Section: Discussionmentioning
confidence: 99%